The feasibility of a DRP margin private product - Engel, Tim (Kansas State University, 2022)
The Dairy Revenue Protection (DRP) of the Federal Crop Insurance Program offered by Risk Management Agency had grown from $95 million in premium in 2019 reinsurance year to $221 million in premium for the 2020 reinsurance and $399 million for the 2021 reinsurance year. With Dairy Revenue Protection being a federally subsidized program and rated by the Risk Management Agency, there is little that an Approved Insurance Provider (AIP) can do to differentiate itself in the market other than to compete with other AIP’s in offering the best service and/or creating differentiation by the means of non-subsidized private insurance products. The tactic of creating private products to differentiate an AIP from the market of competitors has worked before for AIPs, but also can have costly consequences if not rated and marketed appropriately. The purpose of this thesis is to study the feasibility of the DRP private product, DRP Margin Plus, in terms of whether a 65% loss ratio could be achieved and comparatively priced to other risk management tools. The past performance history of Livestock Gross Margin - Dairy, Dairy Revenue Protection, and Dairy Margin Coverage will be evaluated and DRP Margin Plus performance will also be evaluated using the 2019-2021 reinsurance years of livestock gross margin-based feed prices with the volumes of DRP sold to assess how Dairy Margin Plus would have performed. The feasibility of the private product is evaluated based on its loss ratio and its payouts by comparing with those of the alternative products.
Keywords: Agribusiness; Insurance; Margin; Feasibility; Revenue protection